Flow field analysis of columnar vortex - How, Wai Hong. (2009)
This report reviews the flow visualization and Particle Image Velocimetry (PIV) experiments and analysis done by researchers to demonstrate the vortex breakdown phenomenon. Various theories regarding vortex breakdown phenomenon are also explained. Flow visualization was performed in order to study the key characteristics of the spiral-type vortex breakdown. The main qualitative analysis came from Particle Image Velocimetry (PIV) in an attempt to capture the vortex breakdown process in the flow within a confined circular pipe. The 2-D velocity fields were projected on the PIV images to show the occurrence of flow divergence and recirculation zones. The vorticity fields were also created to support the analysis. A comparison between observations from both flow visualization and PIV experiments was also performed.